Factor affecting technical efficiency of the banking sector: Evidence from Ethiopia - Salah Mohammed Abdulahi; Mekonnen Kumlachew Yitayaw; Habtamu Legese Feyisa; Wondmagegn Biru Mamo (Cogent Economics & Finance, 2023)
An efficient bank is more robust to shocks, fosters competitiveness, and promotes stability of the financial system. This study estimates Ethiopia's commercial banks' level of efficiency and its determinants during the period 2014-2020. Data Envelopment Analysis (DEA), Malmquist DEA, and Tobit regression were employed to analyze the data. The result indicated that the average efficiency score of banks in the constant returns to scale (CRS), variable returns to scale (VRS), and scale efficiency (SE) models were 95.5%, 99.85%, and 96.95% , respectively. Furthermore, in the VRS model, a state bank is more efficient than private banks. During the study period, the Total Factor Productivity (TFP) of Banks improved by 1%. According to the Tobit model, the efficiency of banks grows with an increment in the number of branches, bank size, and credit risk. However, when, liquidity risk and the log of the fixed asset increase, bank efficiency will decrease. The level of capitalization, log of GDP, and inflation, on the other hand, do not influence bank efficiency. Therefore, banks should pay close attention to aspects that influence technical efficiency.
Keywords: G21; G32; G24; 330; Tobit; DEA; Bank efficiency; CRS; Malmquist Index; SE; VRS